2016
DOI: 10.1080/19425120.2016.1180333
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study of the Impact of Repetitive Electrical and Mechanical Stimulation on Brown Shrimp Crangon crangon

Abstract: Pulse trawling is currently the best available alternative to beam trawling in the brown shrimp Crangon crangon and Sole Solea solea (also known as Solea vulgaris) fisheries. To evaluate the effect of repetitive exposure to electrical fields, brown shrimp were exposed to the commercial electrodes and pulse settings used to catch brown shrimp (shrimp startle pulse) or Sole (Sole cramp pulse) 20 times in 4 d and monitored for up to 14 d after the first exposure. Survival, egg loss, molting, and the degree of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 16 publications
5
30
0
Order By: Relevance
“…The inferred reduction in mortality rate is related to the effect of mechanical disturbance, primarily due to the replacement of tickler chains. Whether electrical stimulation results in any additional mortality under marine circumstances is yet unknown, but laboratory evidence suggests that exposure to a pulse stimulus will not result in a measurable additional mortality (Soetaert et al 2015b(Soetaert et al , 2016ICES, 2018).…”
Section: Depth Of Disturbance and Sediment Reworkingmentioning
confidence: 99%
“…The inferred reduction in mortality rate is related to the effect of mechanical disturbance, primarily due to the replacement of tickler chains. Whether electrical stimulation results in any additional mortality under marine circumstances is yet unknown, but laboratory evidence suggests that exposure to a pulse stimulus will not result in a measurable additional mortality (Soetaert et al 2015b(Soetaert et al , 2016ICES, 2018).…”
Section: Depth Of Disturbance and Sediment Reworkingmentioning
confidence: 99%
“…Exposure of sole to a broad range of electric stimuli could also not provoque lesions or mortality (Soetaert et al, 2016a). Finally, no increased impact of electric cramp stimuli compared to conventional mechanical stimulation has been evidenced for invertebrate species either (Smaal and Brummelhuis, 2005;van Marlen et al, 2009;Soetaert et al, 2014;2016c). The second part of the present study therefore investigated the effect of an electric cramp stimulus on the escape behaviour of marketable sole through the panel.…”
Section: Introductionmentioning
confidence: 84%
“…This does not surprise as lab experiments reported that the behavioural reaction to a cramp stimulus of most benthic invertebrates was limited: Echinodermata showed no reaction, molluscs retreated in their shells and crabs demonstrated no or hampered movement (Smaal and Brummelhuis, 2005;van Marlen et al, 2009). Shrimp however, show jump and escape behaviour when exposed to electric stimuli Soetaert et al, 2014Soetaert et al, , 2016c, which may promote escape through the panel, the side or the back of the net resulting in the observed higher loss.…”
Section: Brp Vs Ebrpmentioning
confidence: 99%
See 2 more Smart Citations